THE COMPLEX USE OF LOCAL TYPES OF FUEL IN THE POROUS CONSTRUCTION MATERIALS PRODUCTION - N. P. Voronova; B. V. Lesun (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2014)
The article presents a comprehensive low-waste technology is the use of local fuels, which can be used in the technology of some porous building materials. Also provides new methods of preparation of porous building materials based on aggloporite using local fuels and waste energy on the basis of milled peat, fuel briquettes and wood chips allow to replace expensive imported components that comprise the raw mixtures (coal, anthracite).On the basis of mathematical modeling of cooling in reheat furnaces pusher drive developed a method of engineering calculation mode batch hardening in agglomeration. Submitted constructive solution for the development of the cooling charge with thermophysical rational justification cooling modes. A study of the temperature distribution within the charge depending on the different speeds of the belt sintering machine, and hence on the cooling time.The characteristics of the raw material deposits "Fanipol" and the optimal composition of the charge which includes loam, coal, milled peat. In industrial research obtained aggloporite this formulation has shown positive results in strength and density. Established that by decreasing the particle size of the fuel increases the redox potential of the combustion products, which reduces the height of the oxidizing zone and the speed of the sintering raw mix. These processes increase the productivity of sinter machine.Technology is implemented on the "Minsk factory of building materials". The tests analyzed production technology porous construction materials using milled peat with the addition of sawdust. The study results recommend further use of sapropel, which cost significantly lower raw material mixture of submissions and in their physical and mechanical properties much closer to the properties of milled peat.